2013
DOI: 10.5539/ies.v6n4p171
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Helping Teachers: A Professional Development Model that Promotes Teacher Leadership

Abstract: This mixed methods study reports on the outcomes of a professional development model (PDM) developed by a K-12 private school in Beirut, Lebanon, after 3 years of its employment. Specifically, an evaluation of this PDM is provided with special emphasis on its potential of developing teacher leaders at school. The PDM embraces a constructivist approach whereby teachers train colleague teachers and some high school students provide ushering services during professional development events. Data was collected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Before the COVID-19 forced us to act in a new world, it was known that one of the most significant factors in introducing changes to school and in their assimilation is the school principal. Those projects and programs that are encouraged and supported by the principal had the greatest chances of success (Al Harbi, 2014;Ghamrawi, 2013). In the new context, the situation has changed dramatically, and the major responsibility for success has become transferred to teachers, learners, and parents, while the figure of the principal somewhere lost its significance in leading the process.…”
Section: Discussionmentioning
confidence: 99%
“…Before the COVID-19 forced us to act in a new world, it was known that one of the most significant factors in introducing changes to school and in their assimilation is the school principal. Those projects and programs that are encouraged and supported by the principal had the greatest chances of success (Al Harbi, 2014;Ghamrawi, 2013). In the new context, the situation has changed dramatically, and the major responsibility for success has become transferred to teachers, learners, and parents, while the figure of the principal somewhere lost its significance in leading the process.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein of TPD contribution for school improvement, a study by Ghamrawi (2013) revealed that teachers take part in leading PD program nurtures pool for potential teacher leadership that make them more responsible and productive. Besides, OECD (2011) advocated the role of professional development as a tool for lifting the proficiency of teachers.…”
Section: Role Of Tpd In Facilitating Faculty Developmentmentioning
confidence: 99%
“…In all cases, the literature of education supervisors' role and scheme of work may be synthesized into eight areas presented in figure 2. Figure 2 suggests that the education supervisor (From: Ghamrawi (2010Ghamrawi ( , 2011Ghamrawi ( , 2013aGhamrawi ( , 2013b)) 1-Leadership role: which entails distributing leadership, creating cultures and sub-cultures conducive to learning and growth. 2-Activating role: which make the education supervisor responsible for the collaborating and catalyzing teachers to work towards enriching the curricula with all the activities that are conducive to active learning and student-centered classrooms.…”
Section: Roles Played By Supervisorsmentioning
confidence: 99%
“…Thus, while studies from across the globe have focused on teacher professional development and growth through many perspectives and approaches such as school reform (Lieberman & Wood, 2002), training methodologies (Campbell & Malkus, 2011), leadership theories (Ghamrawi, 2013a), school improvement endeavors (Gallagher, Woodworth, & Arshan, 2017); a small number of studies were attentive to the role of educational supervisors in schools in impacting and shaping teacher growth (Wanzare & da Costa, 2000).…”
mentioning
confidence: 99%